2017
DOI: 10.3390/ijms18030492
|View full text |Cite
|
Sign up to set email alerts
|

Hotspot Selective Preference of the Chimeric Sequences Formed in Multiple Displacement Amplification

Abstract: Multiple displacement amplification (MDA) is considered to be a conventional approach to comprehensive amplification from low input DNA. The chimeric reads generated in MDA lead to severe disruption in some studies, including those focusing on heterogeneity, structural variation, and genetic recombination. Meanwhile, the generation of by-products gives a new approach to gain insights into the reaction process of φ29 polymerase. Here, we analyzed 36.7 million chimeras and screened 196 billion chimeric hotspots … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 30 publications
3
9
0
Order By: Relevance
“…The results of the two pipelines demonstrated that the inverted chimeras are the dominant type of the single-end chimeras (average 91.36% by using ChimeraMiner, and average 88.69% by using the previous pipeline). The results were generally in concordance with the results of previous works [6,8,9], which endorsed that ChimeraMiner was accurate in chimera discovering.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…The results of the two pipelines demonstrated that the inverted chimeras are the dominant type of the single-end chimeras (average 91.36% by using ChimeraMiner, and average 88.69% by using the previous pipeline). The results were generally in concordance with the results of previous works [6,8,9], which endorsed that ChimeraMiner was accurate in chimera discovering.…”
Section: Resultssupporting
confidence: 91%
“…In each single cell dataset, the inverted chimera was also the dominant type of the single-end chimera, which was coherent with the results of conventional MDA and previous works [6,8,9]. The consistent ratio between the inverted chimera and direct chimera, in all datasets, demonstrated that the application of ChimeraMiner in single cell MDA datasets was as effective as in conventional MDA datasets.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations